Electronic signature under Iraqi law : a critical examination relating to e-government services - Waheeb, Rana Jabbar (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2015)
Electronic signatures consist of any data in electronic form like letters, characters, numbers or other symbols that are attached to or associated with an electronic transaction or document for the purpose of authentication. The subject of electronic signatures has become a global issue and has the attention of several countries since it impacts on the effectiveness of e-government services. Iraq has attempted to draw a legal framework to regulate electronic signature. Many studies have been done relating to the use of electronic signature from different perspectives. However, few of these studies have examined the challenges and obstacles to the implementation of the Iraqi Act. This thesis examines the electronic signature in the scope of Electronic Signature and Electronic Transactions Act. No78.2012 in Iraq and compares it with other legal frameworks at national and international levels, such as UNCITRAL Model Law in Electronic Signature.2001 and the Digital Signature Act 1997 (Act 562) in Malaysia as well as the Electronic Transactions and Commerce Law No.2 of 2002 in Dubai (UAE). This was done to identify the weaknesses in the Iraqi Act and their impact on the use of e-signature especially in the provision of e-government services. The study found that the Iraqi Act lacks criminalization provisions, information in some Articles, an absence of executive regulation and brushes over the major issue of the lack of technological awareness among Iraqi people. This study also gives recommendations towards further improving and solving the challenges in the Electronic Signature and Electronic Transactions Act in Iraq.